Calcium-dependent cAMP mediates the mechanoresponsive behaviour of endothelial cells to high-frequency nanomechanostimulation. (January 2023) - Ambattu, Lizebona August; Knight, Callum; Lin, Keng-hui; Gelmi, Amy; Yeo, Leslie Y.
Abstract: The endothelial junction plays a central role in regulating intravascular and interstitial tissue permeability. The ability to manipulate its integrity therefore not only facilitates an improved understanding of its underlying molecular mechanisms but also provides insight into potential therapeutic solutions. Herein, we explore the effects of short-duration nanometer-amplitude MHz-order mechanostimulation on interendothelial junction stability and hence the barrier capacity of endothelial monolayers. Following an initial transient in which the endothelial barrier is permeabilised due to Rho–ROCK-activated actin stress fibre formation and junction disruption typical of a cell's response to insults, we observe, quite uniquely, the integrity of the endothelial barrier to not only spontaneously recover but also to be enhanced considerably—without the need for additional stimuli or intervention. Central to this peculiar biphasic response, which has not been observed with other stimuli to date, is the role of second messenger calcium and cyclic adenosine monophosphate (cAMP) signalling. We show that intracellular Ca 2+, modulated by the high frequency excitation, is responsible for activating reorganisation of the actin cytoskeleton in the barrier recovery phase, in which circumferential actin bundles are formed to stabilise the adherens junctions via a cAMP-mediated Epac1–Rap1 pathway. Despite the short-duration stimulation (8 min), the approximate 4-fold enhancement in the transendothelial electrical resistance (TEER) of endothelial cells from different tissue sources, and the corresponding reduction in paracellular permeability, was found to persist over hours. The effect can further be extended through multiple treatments without resulting in hyperpermeabilisation of the barrier, as found with prolonged use of chemical stimuli, through which only 1.1- to 1.2-fold improvement in TEER has been reported. Such an ability to regulate and enhance endothelial barrier capacity is particularly useful in the development of in vitro barrier models that more closely resemble their in vivo counterparts.